Pengembangan Media Video Animasi Berbasis Canva pada Kelas IV Subtema Keberagaman Budaya Bangsaku - Anisa Siti Mubarokah; Lina Novita; Dendy Saeful Zen MF (STKIP Andi Matappa Pangkep, 2023)
The development research is based on the problems found at SDN Layungsari 1 Bogor City. Based on the results of observations, the problems found were that students had not received innovative learning media, students only used theme books in the learning process and This research was developed with the objectives of: (1) developing a product in the form of animated video media in class IV sub-theme 1 cultural diversity of my nation. (2) knowing the feasibility of animated video learning media with validation tests by material experts, media experts, linguists, and the responses obtained from students. This development research uses the ADDIE model. The results of this development research are in the form of a percentage of the validation test scoring by the material expert validator with a score of 88% including the appropriate category, media experts at 94% with the very feasible category and linguists giving a validation score of 100% with the very feasible category. The results of the study show that animated video media is practical and feasible to use. Student responses showed a positive response with the percentage of scores obtained based on student response questionnaires of 90% with a very decent category.